(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2025)
This article explores the effect of experimental ulcerative colitis (EUC) on liver function and estrogen metabolism in rats, as well as the relationship of these factors with endometrial hyperplasia. Ulcerative colitis, a chronic inflammatory disease of the intestine, can exert systemic effects on the body, including impairment of liver function and hormonal balance. In the course of the study, EUC was induced in rats. Morphological changes in liver tissue were assessed, and immunohistochemical (IHC) evaluation of hyperplastic endometrium was performed using the ER marker. The results demonstrated that EUC leads to significant impairments in hepatic function, which in turn affect circulating estrogen levels and its metabolism. Moreover, a strong correlation was observed between disrupted estrogen metabolism and the development of endometrial hyperplasia in EUC-induced rats. These findings indicate a potential mechanism through which intestinal inflammation may influence the reproductive system. The obtained results underscore the importance of investigating the interconnection between intestinal diseases and systemic hormonal alterations, which may have significant clinical implications for understanding disease pathophysiology and developing new therapeutic strategies.